Analysis of Vegetable Farmers' Business Income in Bungi District, Baubau City - Muhammad Hakim Pribadi (JURNAL PENDIDIKAN IPS, 2024)
The food crop subsector plays a strategic role in the lives of most Indonesian people, including vegetable crops. Vegetable crops play an important role as a source of income that can meet the living needs of farmers in the Bungi District. Analysis of vegetable farmers' business income as a first step in determining attitudes towards growing vegetables. In general, vegetable farmers in Bungi District have not calculated their income or capital in detail. This research aims to find out how much income vegetable farmers in Bungi District earn. This research uses a survey method, namely an analytical approach quantitative descriptive. The population and sample in this study were 77 vegetable farmers who were divided into 3 groups. Data collection techniques were carried out using observation, interviews, and documentation. The research results show that a) a new farmer group has emerged, numbering 13 people, with an average net income per planting season of between IDR 2,048,256-IDR 24,3311,000; b) the Mulya Sari farmer group, totaling 17 people, has an average net income per season between Rp. 2,288,372-Rp. 34,562,294; 3) the Mekar Sari II farmer group, totaling 47 people, with a net income per season of IDR 2,223,149 - IDR 35,697,043. So vegetable farmers in Bungi District are said to be feasible and successful when compared to Southeast Sulawesi's UMP of 2,758,984, and vegetable farming is also very efficient (R/C > 1) there.